Steve G. Fancy; Daily energy budgets of caribou: a simulation approach - Skjenneberg (ed.), Sven (Rangifer, 1986)
S.G. Fancy successfully defended his Ph.D. Thesis, «Daily energy budgets of caribou: a simulation approach», at the University of Alaska, Fairbanks, on March 12, 1986.